Necessity of Prophylactic Extrapleural Chest Tube During Primary Surgical Repair of Esophageal Atresia: A Systematic Review and Meta-Analysis - Ladefoged, Martin Riis; Korang, Steven Kwasi; Hildorf, Simone Engmann; Oehlenschlæger, Jacob; Poulsen, Susanne; Fossum, Magdalena; Lausten-Thomsen, Ulrik (Frontiers in Pediatrics, 2022)
Background: Esophageal atresia is corrected surgically by anastomosing and recreating esophageal continuity. To allow the removal of excess fluid and air from the anastomosis, a prophylactic and temporary intraoperative chest tube (IOCT) has traditionally been placed in this area during surgery. However, whether the potential benefits of this prophylactic IOCT overweigh the potential harms is unclear. Objective: To assess the benefits and harms of using a prophylactic IOCT during primary surgical repair of esophageal atresia. Data sources: We conducted a systematic review with a meta-analysis. We searched Cochrane Central Register of Controlled Trials (2021, Issue 12), MEDLINE Ovid, Embase Ovid, CINAHL, and Science Citation Index Expanded and Conference Proceedings Citation Index – (Web of Science). Search was performed from inception until December 3rd 2021. Study selection: Randomized clinical trials (RCT) assessing the effect of a prophylactic IOCT during primary surgical repair of esophageal atresia and observational studies identified during our searches for RCT. Data extraction and synthesis: Two independent reviewers screened studies and performed data extraction. The certainty of the evidence was assessed by GRADE and ROBINS-I. PROSPERO registration: A protocol for this review has been registered on PROSPERO (CRD42021257834). Results: We included three RCTs randomizing 162 neonates, all at overall “some risk of bias”. The studies compared the placement of an IOCT versus none. The meta-analysis did not identify any significant effect of profylacitic IOCT, as confidence intervals were compatible with no effect, but the analyses suggests that the placement of an IOCT might lead to an increase in all-cause mortality (RR 1.66, 95% CI 0.76 to 3.65; three trials), serious adverse events (RR 1.08, 95% CI 0.58 to 2.00; three trials), intervention-requiring pneumothorax (RR 1.65, 95% CI 0.28 to 9.50; two trials), and anastomosis leakage (RR 1.66, 95% CI 0.63 to 4.40).. None of our included studies assessed esophageal stricture or pain. Certainty of evidence was very low for all outcomes. Conclusions: Evidence from RCTs does not support the routine use of a prophylactic IOCT during primary surgical repair of esophageal atresia.